(untitled) (Praxis Educativa, 2023)
We propose, in this writing, to reflect on a didactics that questions received inheritances and understand it in the framework of the Latin American pedagogies Simón Rodríguez, José Martí and Paulo Freire. From there, understanding that teaching is located at the centre of a socio-political system that contributes to community autonomy and awareness, we think of a didactics centred on that political project, in favour of caring for others who remain voiceless, in connection with the territory, with real social problems, and capable of co-designing teaching proposals from decolonial perspectives that offer possibilities of deconstructing hegemonic thinking and constructing new epistemologies.